PENANAMAN NILAI-NILAI MULTIKULTURAL MELALUI PENDIDIKAN AGAMA ISLAM - Nurlaili Amin (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2022)
Abstract:The purpose of this study is to describe the cultivation of multicultural values through Islamic religious education at SMP Negeri 14 Seluma. The subjects of this study were the principal of SMP Negeri 14 Seluma, PAI class VII teachers, and grade VII students of SMP Negeri 14 Seluma. Data analysis techniques are editing, categorization, and interpretation of data. The results of research on the cultivation of multicultural values through Islamic religious education at SMP Negeri 14 Seluma, namely the process of instilling multicultural values through Islamic religious education are given through good habits in the school environment, given activities that can foster social values, and so on. At SMP Negeri 14 Seluma can be said to be good in instilling religious and multicultural values for its students, all efforts are made by the school with the help of all teachers, especially Islamic religious education teachers. Although it still exists, it can still be overcome by the way teachers, especially PAI teachers, always provide continuous and continuous reinforcement in learning in order to grow attitudes that reflect multicultural values, such as tolerance values, democratic values, humanist values, inclusive or open values, and the value of love for the motherland.Keywords: Planting, Values, Multicultural, PAI Abstrak:Penelitian ini bertujuan untuk mendeskripsikan penanaman nilai-nilai multikultural melalui penddikan agama islam di SMP Negeri 14 Seluma . Kepala Sekolah SMP Negeri 14 Seluma, guru PAI kelas VII, dan siswa-siswi kelas VII yang ada SMP Negeri 14 Seluma menjadi subyek dalam penelitian ini. Teknik analisa data menggunakan Editing, kategorisasi, serta penafsiran data. Hasil penelitian dari penanaman nilai-nilai multikultural melalui pendidikan agama islam di SMP Negeri 14 Seluma adalah proses penanaman nilai-nilai multikultural melalui pendidikan agama islam yang diberikan melalui pembiasaan yang baik dilingkungan sekolah, diberikan mermacam kegiatan yang dapat meningkatkan nilai-nilai sosial, serta yang lainnya. Pada SMP Negeri 14 Seluma sudah bisa dikatakan bagus dalam menanamkan nilai-nilai karakter religius dan multikultural untuk siswanya karena semua usaha dikerjakan oleh sekolah dengan bantuan semua guru khususnya guru PAI. Walaupun masih ada tapi hal tersebut masih dapat diatasi dengan strategi guru-guru terutama guru Pendidikan Agama Islam berupaya memberikan penguatan secara kontinue dan berkesinambungan dalam pembelajaran supaya tumbuh sikap yang mencerminkan nilai-nilai multikultural, contohnya nilai toleransi, demokratis, humanis, inklusif atau terbuka, dan nilai cinta tanah air).Kata Kunci: Penanaman, Nilai-nilai, Multikultural, PAI